The Effect of Significant Accounting Policies on Earning Quality of Firms in Lower-Northeast Thailand - บุตรสุวรรณ์, จารุวรรณ (Journal for Developing the Social and Community, 2016)
The disclosing significant accounting policies adopted in the preparation of financial statements should represent a true and fair view, especially earning quality. It is a vital policy which demonstrates the company performance and internal control. The purpose of this study is divided into 3 subjects which are (1) Study the significant accounting policies selected by the firms in Lower-northeast Thailand (2) Investigate the company’s earning quality (3) Analyze the effect of the significant accounting policies selected by the firms in Lower-northeast Thailand. The target populations for this research were 106 limited companies in Lower-northeast Thailand. Fieldwork is taken by questionnaires. The methodology for data analysis was multiple regression analysis and prediction equation. The results revealed that also is shows that all significant accounting policies of generally accepted accounting principles and economic decisions making have a positive impact on earning quality. Therefore, the firms have to earning management as it is relevant to decision making. Moreover, the significant accounting policies selected by the enterprises should comply with accounting standard and be appropriate to their circumstances.